2014
DOI: 10.1111/eva.12189
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale genetic correlates to condition and migration in a wild cervid

Abstract: The relationship between genetic variation and phenotypic traits is fundamental to the study and management of natural populations. Such relationships often are investigated by assessing correlations between phenotypic traits and heterozygosity or genetic differentiation. Using an extensive data set compiled from free-ranging mule deer (Odocoileus hemionus), we combined genetic and ecological data to (i) examine correlations between genetic differentiation and migration timing, (ii) screen for mitochondrial ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 88 publications
(202 reference statements)
3
28
0
Order By: Relevance
“…; Northrup et al . ), our results and work on other taxa suggest that the null hypothesis should be that ungulates can, and do, switch between migratory strategies.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…; Northrup et al . ), our results and work on other taxa suggest that the null hypothesis should be that ungulates can, and do, switch between migratory strategies.…”
Section: Discussionsupporting
confidence: 48%
“…Nelson (1998) clearly showed that migratory behaviour can change from that learned from one's mother in white-tailed deer (Odocoileus virginianus) by following marked mother-daughter pairs over multiple years. Combined with no evidence for genetic determinism for migratory behaviour in ungulates (Barnowe-Meyer et al 2013;Northrup et al 2014), our results and work on other taxa suggest that the null hypothesis should be that ungulates can, and do, switch between migratory strategies.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Despite these difficulties, first attempts to associate the distribution of natural genetic variation with migration traits under selection are emerging (Northrup et al . ; Toews et al . ; Delmore et al .…”
Section: Discussionmentioning
confidence: 99%